Spiniferomonas sibirica sp. nov. (Chrysophyceae, Chromulinales), a new silica-scaled freshwater flagellate - Bessudova, Anna Y.; Firsova, Alena D.; Likhoshway, Yelena V. (Phytotaxa, 2025)
A new species, Spiniferomonas sibirica, has been described using scanning and transmission electron microscopy. It is characterized by a unique combination of three types of plate-scales, each with a single lacuna: elliptical and/or rounded, and rounded-to-ovoid with an incomplete bridge. The morphological relationship of the new taxon with other Spiniferomonas species is discussed. S. sibirica was discovered in the mouths of the main tributaries of the Angara River in Siberia in May, with water temperatures ranging from 11.3 to 14.6 ℃ and pH values of 7.8 to 8.4.